Social networking sites (SNS) as a tool for midwives to enhance social capital for adolescent mothers. (July 2018) - Nolan, Samantha; Hendricks, Joyce; Williamson, Moira; Ferguson, Sally
Highlights: Adolescent mothers suggest midwives could enhance existing online support mechanisms. SNS use by midwives may provide additional parenting support to adolescent mothers. Guideline development considered crucial to innovative midwifery practice provision. Abstract: Objective: to explore ways in which midwives can enhance the support provided by social networking sites for adolescent mothers. Design: a narrative approach was employed to guide the research design and processes. Approval was obtained from Edith Cowan University human ethics department. Setting: focus groups and interviews were undertaken with adolescent mothers and midwives in Western Australia. Findings: the four key themes identified across both groups were validation by midwives, importance of ownership, enhanced community connections and the importance of guideline development. Conclusions: findings suggest both mothers and midwives consider there are a variety of ways in which healthcare professionals could enhance the support afforded to adolescent mothers by their use of SNS. Midwives were more likely to consider the need for guideline development, but the underlying value of accessible, professionally mediated online support and information was consistent across the two groups. Implications for practice: Midwives would benefit from acknowledging the role played by SNS in providing support to adolescent mothers and by considering ways in which this technology can be used to lend further support to this group of mothers.